1997
DOI: 10.1111/j.1365-2044.1997.29-az029.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postoperative myocardial ischaemia  The role of intercurrent arterial hypertension and other cardiovascular risk factors

Abstract: SummaryOne hundred and eighty-three patients were studied to examine the role of a number of risk factors in the development of silent ischaemia after general anaesthesia for general and vascular surgery. We collected evidence of cardiovascular risk factors using a binary questionnaire. The patients were monitored pre-and postoperatively using a Holter ECG monitor. Usable data were collected on 140 patients. Pre-operative silent myocardial ischaemia was found to be strongly associated with postoperative silent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 10 publications
0
42
1
Order By: Relevance
“…Importantly, these 281 patients [6,13,14] are in a lower cardiovascular risk category than those reported in peri-operative beta-blocker studies, where major cardiovascular complications have been reported (Table 2). The occurrence of cardiovascular outcomes over the 12 months postsurgery for the two patient groups is recorded in Table 4.…”
Section: Patient Demographics and Surgical Riskmentioning
confidence: 75%
See 4 more Smart Citations
“…Importantly, these 281 patients [6,13,14] are in a lower cardiovascular risk category than those reported in peri-operative beta-blocker studies, where major cardiovascular complications have been reported (Table 2). The occurrence of cardiovascular outcomes over the 12 months postsurgery for the two patient groups is recorded in Table 4.…”
Section: Patient Demographics and Surgical Riskmentioning
confidence: 75%
“…Values are number (proportion). In the comparator chronic beta-blocked group [6,13,14], the incidence of silent myocardial ischaemia was 38%. those patients exhibiting peri-operative SMI (p = 0.036).…”
Section: Patient Demographics and Surgical Riskmentioning
confidence: 99%
See 3 more Smart Citations